Phytochemicals Compound and Antioxidant Activity of Tradescantia spathacea Sw. Leaf Extracts - Fikroh, Retno Aliyatul; Hidayah, Muhamad Aditya (Biology, Medicine, & Natural Product Chemistry, 2025)
Tradescantia spathacea Sw. is commonly used as a traditional medicine plant to treat several diseases. This study aims to identify phytochemical constituents using phytochemical screening, quantify the total phenolic (TPC) and flavonoid content (TFC) analysis, and evaluate the antioxidant activity of various extracts via DPPH free radical scavenging activity. The phytochemical constituent revealed the presence of bioactive compounds such as flavonoid, alkaloid, saponin, steroid, triterpenoid, and tannin in different extracts of Tradescantia spathacea Sw. leaf. The methanolic leaf extract showed the best total phenolic and flavonoid content values of 83.35±0.00 mgGAE/g and 33.79±0.13 mg/g, respectively. Methanolic extracts also showed potent antioxidant activity in the DPPH assay with IC50 values of 80,835 µg/mL. The results suggest that Tradescantia spathacea Sw. could be an alternative source of natural antioxidant agents.